L’élection présidentielle de 2015 en Côte d’Ivoire : une victoire pour Ouattara, mais pas un plébiscite - Christian Bouquet; Irène Kassi-Djodjo (EchoGéo)
The presidential election recently held in Côte d'Ivoire was peaceful and, unlike the previous poll in 2010, its results have not been disputed. Facing a weakened and divided opposition, Alassane Ouattara won with 83.66 %  of the votes cast. However, the turnout was relatively low (52.86%) and his score out of the 6 301 189 registered voters was only 41.55%. In absolute value, the outgoing president gained the same total amount of votes compared to 2010 while regressing in Abidjan, including his traditional strongholds (Abobo, Adjame), despite new and remarkable infrastructures benefitting the megacity which might have prompted a more robust adhesion from voters.